The Relationship Between Body Weight, Age, and Blood TSH Hormone Levels in a Sample of Women Attending Misurata Central Laboratory - Soukaynah Ahmed Omer Hareebah; Raja Abdullah Mohammed Aljibali; Esra Ahmed Abu-Shregh; Maryam Abd-Alsalam Ateyah; Hanady Ahmed Abu-Shregh; hunydah Alhussen shnab (Libyan Journal of Medical and Applied Sciences, 2025)
Thyroid disorders are widespread global health issues with a significant impact on public health. This study aimed to investigate the relationship between body weight, age, and thyroid-stimulating hormone (TSH) levels in a sample of 150 women attending the Misurata Central Laboratory. Blood samples were collected during January and February 2025, and TSH levels were analyzed using the Cobas e 411 analyzer. The results indicate that 18.47% of the women had normal TSH levels, 1.33% had elevated levels, and 80.20% had low levels. Analysis of variance (ANOVA) revealed a statically significant difference (P-Value = 0.000) between the TSH, weight, age groups. Women with higher body weight in the 30-39 age category recorded the highest TSH values. However, the Pearson correlation coefficient showed a very weak and non-significant correlation between TSH and both weight (r=0.097) and age (r=0.068). The study concluded that while ANOVA indicate significant difference among the groups, the direct correlation between the variable of weight and age with TSH was weak. These findings highlight the complexity of the relationship between these variables and recommended further research with larger sample sizes to explore this association more deeply.